Potensi Ampas Kelapa sebagai Bahan Substitusi Brownies Cookies - Livia Widyanti; Cici Rahmadani Chaya Nirmala; Hanifah Nurul Izza; Esteria Priyanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The utilization of coconut dregs not only provides added value to brownies cookies products, but also contributes to reducing waste generated from the coconut industry. The purpose of this study was to produce brownies cookies substituted by coconut dregs with acceptable sensory characteristics and has the potential to be an interesting entrepreneurial idea. This study uses the 4D Research and Development (R&D) model which includes 4 (four) research stages including the define stage to analyze research needs, the design stage to design research, the developtment stage for the product development process, and the disseminate stage for product distribution. This study produced a brownie cookies product called BROKA (BRownies cOokies ampas KelapA). BROKA has a sweet taste balanced with coconut flavor, a distinctive brownies aroma, and a soft and crunchy texture. This product also displays a dark brown color on the brownies and light brown on the soft cookies. In 1 (one) BROKA recipe can produce 33 servings. Each 1 (one) serving of BROKA contains 26,82 Kcal of energy, 0,35 g of protein, 1,19 g of fat, and 2,93 g of carbohydrates. It can be concluded that coconut dregs have great potential as a substitute ingredient in making brownies cookies and can be an interesting entrepreneurial idea.